2019
DOI: 10.1186/s12904-019-0472-z
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on decision and documentation of refraining from resuscitation in two medical home care units in Sweden

Abstract: Background A decision to refrain from cardiopulmonary resuscitation (CPR) in the case of cardiac arrest is recommended in terminally ill patients to avoid unnecessary suffering at time of death. The aim of this study was to describe the frequency of decisions and documentation of “do not attempt cardiopulmonary resuscitation” (DNACPR) in two Medical Home Care Units in Stockholm. Unit A had written guidelines about how to document CPR-decisions in the medical records, including a requirement for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…These results suggest some dissonance between patients and healthcare providers with regard to aggressive treatment, LST, and limited medical care, which are considered to be quality indicators for EOL discussion [23][24][25][26]. The previous studies demonstrated, the general public has poor knowledge regarding the benefits of aggressive treatment and LST, such as CPR, parenteral nutrition, and hydration, for terminally ill cancer patients [27,28]. Therefore, the general public might overestimate the success rate of CPR and the benefit of parenteral nutrition and hydration in late-stage cancer patients.…”
Section: Discussionmentioning
confidence: 95%
“…These results suggest some dissonance between patients and healthcare providers with regard to aggressive treatment, LST, and limited medical care, which are considered to be quality indicators for EOL discussion [23][24][25][26]. The previous studies demonstrated, the general public has poor knowledge regarding the benefits of aggressive treatment and LST, such as CPR, parenteral nutrition, and hydration, for terminally ill cancer patients [27,28]. Therefore, the general public might overestimate the success rate of CPR and the benefit of parenteral nutrition and hydration in late-stage cancer patients.…”
Section: Discussionmentioning
confidence: 95%
“…One of these targeted cases is crisis management during home emergencies. A number of studies have discussed that the ability to manage acute conditions such as home resuscitation by a nurse and the correct reaction to it can imply safe care [ 44 ]. Another targeted safety case is medication safety.…”
Section: Discussionmentioning
confidence: 99%
“…The median length of care is between three to four months. More details about the unit can be found elsewhere [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%